Meningkatkan Tanggung Jawab Belajar Siswa di Rumah Selama Covid 19 melalui Pendekatan Konseling Kelompok Realita: (Studi Kasus Siswa Kelas X1 SMA Negeri 2 Lambu) (Jurusan Bimbingan dan Konseling Islam, 2021)
This study discusses efforts to increase learning responsibility for students of SMA Negeri 2 Lambu class XI by using a reality group counseling approach. This study uses qualitative research methods with a case study approach. The research subjects consisted of 12 students who will take part in the counseling process, namely pre-counseling, the initial stage, the transition stage, the work stage, and the final stage. The reality group counseling used emphasizes students' awareness of their responsibilities as students, such as; learn during class hours, do assignments from the teacher, be able to determine the choice of learning activities from various alternatives and have a strong interest in learning. Based on the results of the study, it was found that the implementation of reality group counseling could increase students' learning responsibilities. This can be seen by changes in students' behavior and mindset. Among them are self-control, discipline and confidence in learning.